The value of sensitive imaging modalities in rheumatoid arthritis. - Taylor, P (2003)
X-ray evaluation of rheumatoid joints is relatively inexpensive, is widely available and has standardised methods for interpretation. It also has limitations, including the inability to reliably determine structural change in less than 6-12 months, the need for experienced readers to interpret images and the limited acceptance of this technique in routine clinical practice. High-frequency ultrasound, with or without power Doppler, and magnetic resonance imaging of rheumatoid joints permit an increasingly refined analysis of anatomic detail. However, further research using these sensitive imaging technologies is required to delineate pathophysiological correlates of imaging abnormalities and to standardise methods for assessment.